1996
DOI: 10.1164/ajrccm.154.3.8810612
|View full text |Cite
|
Sign up to set email alerts
|

Cytokeratins as serum markers in lung cancer: a comparison of CYFRA 21-1 and TPS.

Abstract: We examined two recently described cytokeratin markers, CYFRA 21-1 (cytokeratin fragment recognized by KS 19-1 and BM 19-21 antibodies) and TPS (specific M3 epitope of the tissue polypeptide antigen), in 405 lung cancer patients (91 small-cell and 314 non-small-cell lung cancers) and 59 patients presenting with nonmalignant pulmonary disease. Sensitivity-specificity relationship, as analyzed by receiver operating characteristic curves, demonstrated a higher accuracy of CYFRA 21-1 in comparison with TPS in both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
35
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(37 citation statements)
references
References 18 publications
2
35
0
Order By: Relevance
“…However, in our study, the prognostic value of Cyfra 21-1 is independent of the stage of the disease. Our findings are in agreement with those of Pujol et al (Pujol et al, 1993(Pujol et al, , 1996, who report that the prognostic significance obtained by Cyfra 21-1 in squamous cell lung cancer is independent and adds to the information obtained from other classic prognostic factors, such as extent of the disease, weight loss, performance status, etc. Niklinski and colleagues report that Cyfra 21-1 may be an independent prognostic parameter of survival and tumour relapse in squamous cell lung cancer (Niklinski et al, 1996).…”
Section: Discussionsupporting
confidence: 93%
“…However, in our study, the prognostic value of Cyfra 21-1 is independent of the stage of the disease. Our findings are in agreement with those of Pujol et al (Pujol et al, 1993(Pujol et al, , 1996, who report that the prognostic significance obtained by Cyfra 21-1 in squamous cell lung cancer is independent and adds to the information obtained from other classic prognostic factors, such as extent of the disease, weight loss, performance status, etc. Niklinski and colleagues report that Cyfra 21-1 may be an independent prognostic parameter of survival and tumour relapse in squamous cell lung cancer (Niklinski et al, 1996).…”
Section: Discussionsupporting
confidence: 93%
“…By analysing the different prognostic studies (Ebert et al, 1993(Ebert et al, , 1997Pujol et al, 1993aPujol et al, , 1996Pujol et al, , 2001aGiovanella et al, 1995;Moro et al, 1995;Paesmans et al, 1995a;Wieskopf et al, 1995;Szturmowicz et al, 1996;Brechot et al, 1997;Hamzaoui et al, 1997;Takei et al, 1997;Hirashima et al, 1998;Niklinski et al, 1998;Nisman et al, 1998Nisman et al, , 1999Foa et al, 1999;Kashiwabara et al, 2000;Buccheri et al, 2003), one can observe that there are some uncertainties regarding the exact hazard ratio of risk of death associated with a high serum CYFRA 21-1 level insofar as the estimated values range from 1.05 (Moro et al, 1995) to 2.8 (Wieskopf et al, 1995). This discrepancy is puzzling and might reflect both the relatively small size of the studies and the inconstancy of co-variables introduced in the proportional hazards model.…”
mentioning
confidence: 99%
“…The values of both Cyfra 21-1 and TPS significantly reflected the disease stage in NSCLC. However, when multivariate analysis was performed to take into account other significant factors, only Cyfra 21-1, and not TPS, was confirmed to be an independent prognostic factor (Pujol et al, 1996).…”
Section: Circulating Cytokeratin-related Molecules and Their Biologicmentioning
confidence: 89%
“…Studies of patients with lung diseases of either neoplastic or non-neoplastic origin revealed TPS sensitivity rates between 13-54% (Correale et al, 1994;Giovanella et al, 1995;Nisman et al, 1998;Pujol et al, 1994;Pujol et al, 1996;van der Gaast et al, 1994). TPS sensitivity did not vary in NSCLC with different histology, but it did differ according to the progression of lung cancer (Giovanella et al, 1995;Pujol et al, 1996).…”
Section: Circulating Cytokeratin-related Molecules and Their Biologicmentioning
confidence: 99%
See 1 more Smart Citation